PENYULUHAN PENCEGAHAN TINDAK KRIMINAL ONLINE KEPADA IBU-IBU DASAWISMA DI RW 10 KELURAHAN CIRACAS "CYBERGUARD: PEMAHAMAN DAN KEAMANAN ONLINE" - Neny Rosmawarni; Ridwan Raafi’udin; Catur Nugrahaeni Puspita Dewi; Fajar Edyana (Jurnal Abdimas Bina Bangsa, 2024)
The rapid development of information technology brings with it various risks, including an increase in online crime. Groups of dasawisma women in RW 10 Ciracas Village are often easy targets for fraud and cybercrime due to a lack of understanding of online security. The "CyberGuard" counseling program is designed to increase awareness and knowledge about the prevention of online crime among dasawisma mothers. Through a series of workshops and educational sessions, the program provides information on the types of cybercrime, signs of online fraud, and preventive steps that can be taken to protect yourself and your family. The results of the evaluation showed a significant increase in the participants' understanding and awareness of online security, as well as their ability to identify and avoid potential cyber threats. This program is expected to be a model for similar counseling in other communities to improve the digital safety of the community at large